Strategi Pemberdayaan Masyarakat Berbasis Kearifan Lokal untuk Membangun Kemandirian Ekonomi, Ketahanan Sosial, dan Pelestarian Lingkungan di Perbatasan Entikong, Indonesia-Malaysia - Muhammad Nur Imanulyaqin; Imran Imran; Zuri Astari; Patrisia Rahayu Utami (Universitas Pendidikan Ganesha, 2025)
This study examines community empowerment strategies based on local wisdom in the border area of Entikong, Sanggau Regency, West Kalimantan, Indonesia. The research focuses on three key dimensions—economic self-reliance, social resilience, and environmental sustainability. Using a qualitative and descriptive approach, data were gathered through in-depth interviews, participatory observations, and documentation involving village leaders, community institutions, and residents. The findings reveal that integrating local wisdom such as gotong royong (mutual cooperation), customary law, and traditional cultural practices strengthens social cohesion, enhances citizen participation, and promotes ecological balance. The Village Development Planning Forum (Musrenbang) functions as a participatory mechanism that aligns empowerment initiatives with community needs. However, challenges persist in product marketing and institutional capacity-building. The study concludes that local wisdom-based empowerment fosters sustainable community development when programs are socially and culturally adaptive. Theoretically, this research contributes to the discourse on culture-based empowerment within borderland studies, while practically, it offers a model for designing participatory and context-sensitive empowerment strategies applicable to other frontier regions.